2005
DOI: 10.1080/01443610500231393
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of correct use of a seatbelt among pregnant women and health professionals: A multicentric survey

Abstract: A questionnaire survey was conducted to determine if pregnant women and healthcare professionals were aware of the correct use of a seatbelt and if advice was given. A total of 154 pregnant women and 56 health professionals were included in the study. A total of 115 (74.6 %) pregnant women wore seatbelts as drivers; 51 (33.1%) women were concerned about wearing the seatbelt in pregnancy; eight (14.2 %) received advice from health professionals. Incorrect positioning of a seatbelt was indicated by 67 (43.5 %) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…in 40% to 50% of pregnant women. 5,6 Various other studies have shown reduced seatbelt compliance during pregnancy. 7 The proportion of seatbelt use has been reported to be around 70% to 80% before pregnancy, but reduced by half at 20 weeks or more of gestation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…in 40% to 50% of pregnant women. 5,6 Various other studies have shown reduced seatbelt compliance during pregnancy. 7 The proportion of seatbelt use has been reported to be around 70% to 80% before pregnancy, but reduced by half at 20 weeks or more of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…7 The proportion of seatbelt use has been reported to be around 70% to 80% before pregnancy, but reduced by half at 20 weeks or more of gestation. 5,7 There is also evidence that pregnant women lack information about the proper use of a seatbelt and its role in preventing injury: only 14% to 37% of pregnant women received advice from health care professionals. [5][6][7][8] The common reasons for not using a seatbelt have been reported to include discomfort, inconvenience, forgetfulness, and fear of harming the fetus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…51 One-third of the women reported concerns about wearing a seat belt during pregnancy and only 22% reported that they received belt use advice during pregnancy. 51 …”
Section: Motor Vehicle Safety Interventionsmentioning
confidence: 99%
“…Therefore, a low rate of seatbelt use among women throughout pregnancy is a nationwide problem. According to a self-administrated questionnaire survey at obstetric clinics in suburban areas of Japan, only about one third of pregnant women use seatbelts consistently at a gestational age of 30 weeks or more which was extremely lower than UK (74.6%) or USA (83.8%) [4][5][6]. By being exempted from the required use seatbelts, pregnant women in Japan and their fetuses are at an increased risk of fatal injuries.…”
mentioning
confidence: 97%